Exploring Music Effects on Human Emotion Emerging Through EEG: A Systematic Literature Review (Journal of Cortexplore, 2026)
This comprehensive review investigates the intricate relationship between music and brain activity, focusing on insights gleaned from electroencephalography (EEG) studies. Music's impact on cognition, emotion, and behaviour is examined through the lens of EEG signals, elucidating the neural mechanisms underlying musical perception and processing. Rhythmic entrainment, emotional modulation, and cross-modal integration are explored as fundamental aspects of music-brain interactions. Clinical applications, therapeutic interventions, and future directions in music neuroscience are discussed, highlighting the potential for personalized interventions and cognitive enhancement. By synthesizing findings from diverse disciplines, this review underscores the transformative power in promoting health, cognitive vitality and well-being by music. Embracing interdisciplinary collaboration and technological innovation, we can continue to explore in depth of music's involvement on the brain and harness its therapeutic potential for the benefit of EEG and giving a brief information of EEG signal and its Technologies and process of signal acquiring.DOI: doi.org/10.65320/jce.vol.1.issue1.7
Keywords: Music neuroscience; EEG; Neural correlates; Cognitive functions; Emotional responses; Rhythmic synchronization; Therapeutic potential; Technological innovation; EEG signals; Different frequency bands